Integrating 5G-U with time-sensitive networking for industrial Internet: architectures and technologies - Yueping CAI; Dong LI; Chi XU; Zhen WANG; Xiaowen ZHANG (Tongxin xuebao)
Industrial Internet is one of enabling technologies for Industry 4.0.Networking is one indispensible technology of industrial Internet.The traffic types and communication requirements of typical industrial services were analyzed first.TSN (time-sensitive networking) and 5G-U (5G unlicensed) were considered as the promising wireline and wireless solutions for industrial Internet, respectively.The integration network architectures of 5G-U and TSN were presented based on four models, which included 5G-U as TSN networks, links, bridges/switches, and TSN as transport networks of 5G-U.The key technologies of the integrated architectures were integrations of time-synchronization plane, data plane, and control plane.Finally, research challenges and potential research directions in the filed were discussed.